Using Youth Sport to Enhance Parents' Sense of Community - Stacy Warner; Marlene Dixon; Stephen Leierer (Journal of Applied Sports Management, 2015)
Youth sport is a large and influential sector of the sport industry. This sector has received considerable attention regarding issues such as improving participants' experiences and attracting and retaining more participants. Parents are also highly involved in youth sport, yet their experiences are less understood. This study ex-amines the role a youth sport program plays in fostering a sense of community for parents. Using a qualitative interpretative design, participants were drawn from a youth sport program in the United States. The focus group data ( n = 36) revealed that The Child's Experience, Clear Logistics , Administrative Consideration , and Eq-uity in Administrative Decisions were the most salient elements that influenced sense of community for youth sport parents. Implications for practice are dis-cussed.
Keywords: youth sport; parents; community; sense of community